2018
DOI: 10.3390/foods7070108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Iodine Feeding on Microbiological and Physico-Chemical Characteristics and Biogenic Amines Content in a Raw Ewes’ Milk Cheese

Abstract: Iodine is an essential trace element involved in the regulation of thyroid metabolism and antioxidant status in humans and animals. The aim of this study was to evaluate the effect of ewes’ dietary iodine supplementation on biogenic amines content as well as microbiological and physico-chemical characteristics in a raw milk cheese at different ripening times (milk, curd, and 2, 7, 15, 30, 60, and 90 days). Two cheese-making trials were carried out using milk from ewes fed with unifeed (Cheese A) or with the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The FAAs content increased significantly during ripening in all samples, reaching values of 233.74, 252.54 and 296.84 mg leucine/g in R1, R2 and R3 cheeses respectively after 270 days of ripening. This increase is in agreement with previous observations in Caciocavallo Pugliese, in Picante cheese, in Kashkaval cheese and in other Pecorino cheeses [9,55,56,57,58]. The greater proteolytic activity in R3 cheeses was in agreement with Tofalo et al, (2015) [9] who observed a higher proteolytic activity for pig rennet than for calf and kid ones.…”
Section: Resultssupporting
confidence: 93%
“…The FAAs content increased significantly during ripening in all samples, reaching values of 233.74, 252.54 and 296.84 mg leucine/g in R1, R2 and R3 cheeses respectively after 270 days of ripening. This increase is in agreement with previous observations in Caciocavallo Pugliese, in Picante cheese, in Kashkaval cheese and in other Pecorino cheeses [9,55,56,57,58]. The greater proteolytic activity in R3 cheeses was in agreement with Tofalo et al, (2015) [9] who observed a higher proteolytic activity for pig rennet than for calf and kid ones.…”
Section: Resultssupporting
confidence: 93%
“…The excessive proteolysis in cheeses subjected to an uncontrolled ripening in terms of environmental conditions and duration leads to the formation of high concentrations of FAAs that can be decarboxylated, mainly by non-starter LAB, with the consequent release of biogenic amines, which are associated with poor flavor and potentially negative effects on consumer health. The most relevant biogenic amines are represented by histamine, tyramine, cadaverine, and putrescine, which are respectively synthesized starting from histidine, tyrosine, lysine, and ornithine [24].…”
Section: Metabolism Of Free Amino Acids (Faa)mentioning
confidence: 99%
“…Importantly, the increase in iodine did not result in a quantitative modification of other substances examined in milk and cheese. Our data confirm earlier studies showing unchanged gross composition in both sheep products (Schirone et al ., 2018; Iannaccone et al ., 2020) and cattle products (Iannaccone et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%